2019
DOI: 10.1016/j.actpsy.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in perceptual hand maps: A meta-analysis

Abstract: A large body of research has suggested that localisation of the hand in external space relies on distorted representations of the hand. We developed a paradigm for measuring implicit perceptual maps of the hand (Longo & Haggard, 2010, Proc Natl Acad Sci USA, 107, 11727-11732), which show systematic deviation from actual hand shape, including overestimation of hand width and underestimation of finger length. Recently, Coelho and Gonzalez (in press, Psychol Res) reported sex differences in these perceptual hand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 135 publications
(133 reference statements)
0
16
1
Order By: Relevance
“…Our findings that there are no differences between how males and females perceive their hand size is not compatible with what has been found in previous studies that looked at sex differences in hand representation [6,20]. Longo [6] recently conducted a meta-analysis of nineteen experiments that used his 'psychomorphometric paradigm' method of mapping the body [1] to examine whether sex differences exist for perceptual hand maps. He concluded that distortions occurred for both males and females but that sex differences exist in the magnitude of distortions in perceptual hand maps, with women showing greater overestimation of hand width and men showing greater underestimation of finger length.…”
Section: Sex and Body Satisfaction Scorescontrasting
confidence: 64%
See 2 more Smart Citations
“…Our findings that there are no differences between how males and females perceive their hand size is not compatible with what has been found in previous studies that looked at sex differences in hand representation [6,20]. Longo [6] recently conducted a meta-analysis of nineteen experiments that used his 'psychomorphometric paradigm' method of mapping the body [1] to examine whether sex differences exist for perceptual hand maps. He concluded that distortions occurred for both males and females but that sex differences exist in the magnitude of distortions in perceptual hand maps, with women showing greater overestimation of hand width and men showing greater underestimation of finger length.…”
Section: Sex and Body Satisfaction Scorescontrasting
confidence: 64%
“…They found that finger length was underestimated in both sexes but hand width was only overestimated in women. Longo [6] speculates that these differences could be explained by how actual hand size (used as a reference) was measured-using a photograph of the hand next to a ruler in his studies compared to Coelho and Gonzalez's method of pointing to landmarks on a non-occluded hand. The latter may not provide an accurate reference due to potential motor control or visual biases with which such localization tasks may be associated.…”
Section: Sex and Body Satisfaction Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study found greater finger length underestimation and reduced hand width overestimation in male participants compared to female participants [ 20 ]. However, these differences were minimized when the participants’ actual hand size was modeled as a covariate, suggesting that they are likely to be related to the physical properties of the hand, rather than to a gender asymmetry, per se [ 8 ]. In detail, authors put forward the possibility that the hand structure may be distorted toward a prototypical hand [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the full body was perceived as thinner (underestimating width) in the front and back views but when the body was viewed from the side, only females overestimated their width. A parallel can be found in emerging sex differences in hand perception where overestimation of hand width is larger in females (Coelho and Gonzalez, 2019;Longo, 2019). The height of the body was perceived as accurate.…”
Section: Discussionmentioning
confidence: 81%